VC - A method for estimating time-varying coefficients in linear models - Ekkehart Schlicht (Kiel Institute for the World Economy (IfW), 2019)
This paper describes a moments estimator for a standard state-space model with coefficients generated by a random walk. This estimator does not require that disturbances are normally distributed, but if they are, the proposed estimator is asymptotically equivalent to the maximum likelihood estimator.
Keywords: C2; C22; C32; C51; C52; 330; time-series analysis; linear model; state-space estimation; time-varying coefficients; moments estimation